Transcriptome Analysis During Follicle Development in Turkey Hens With Low and High Egg Production - Brady, Kristen; Liu, Hsiao-Ching; Hicks, Julie A.; Long, Julie A.; Porter, Tom E. (Frontiers in Genetics, 2021)
Low and high egg producing hens exhibit gene expression differences related to ovarian steroidogenesis. High egg producing hens display increased expression of genes involved in progesterone and estradiol production, in the granulosa layer of the largest follicle (F1G) and small white follicles (SWF), respectively, whereas low egg producing hens display increased expression of genes related to progesterone and androgen production in the granulosa (F5G) and theca interna layer (F5I) of the fifth largest follicle, respectively. Transcriptome analysis was performed on F1G, F5G, F5I, and SWF samples from low and high egg producing hens to identify novel regulators of ovarian steroidogenesis. In total, 12,221 differentially expressed genes (DEGs) were identified between low and high egg producing hens across the four cell types examined. Pathway analysis implied differential regulation of the hypothalamo-pituitary-thyroid (HPT) axis, particularly thyroid hormone transporters and thyroid hormone receptors, and of estradiol signaling in low and high egg producing hens. The HPT axis showed up-regulation in high egg producing hens in less mature follicles but up-regulation in low egg producing hens in more mature follicles. Estradiol signaling exclusively exhibited up-regulation in high egg producing hens. Treatment of SWF cells from low and high egg producing hens with thyroid hormone in vitro decreased estradiol production in cells from high egg producing hens to the levels seen in cells from low egg producing hens, whereas thyroid hormone treatment did not impact estradiol production in cells from low egg producing hens. Transcriptome analysis of the major cell types involved in steroidogenesis inferred the involvement of the HPT axis and estradiol signaling in the regulation of differential steroid hormone production seen among hens with different egg production levels.